Efficacy of a bismuth-based quadruple therapy regimen for Helicobacter pylori eradication in Saudi Arabia - Alsohaibani, Fahad (Saudi J Gastroenterol, 2020)
BACKGROUND/AIM: The treatment efficacy of Helicobacter pylori (H. pylori) has been decreasing over time due to resistance to multiple antimicrobial therapies. The most effective treatment regimen for Saudi Arabian patients infected with H. pylori is still unknown. We aimed to study the eradication rate of 10 days of quadruple therapy; bismuth subcitrate potassium 140 mg, metronidazole 125 mg, and tetracycline 125 mg for H. pylori infection in a Saudi population. PATIENTS AND METHODS: This was a prospective, open-label, non-randomized controlled trial. Patients with H. pylori infection were diagnosed by upper gastrointestinal (GI) endoscopy and rapid urease test (RUT) or histology. Patients who tested positive were recruited. Eligible patients were prescribed a 10-day course of quadruple therapy and received three capsules 4 times daily for 10 days along with omeprazole 20 mg twice daily. H. pylori was considered eradicated if the urea breath test (UBT) was negative after 6 weeks of completing the treatment. RESULTS: Ninety-two patients with H. pylori infection were recruited. Three patients withdrew from the trial and another seven patients lost follow-up. We analyzed 82 patient's data as per-protocol analysis, of whom 66 (80%) were naive to H. pylori treatment. Four patients had failed previous treatment with the sequential regimen and 12 patients had treatment with clarithromycin-based triple therapy. The post-treatment UBT for H. pylori infection was negative by per-protocol analysis in 72/82 patients (87.8%), and 72/92 (78.3%) by intention-to-treat analysis. There was no correlation between previous treatment failure and treatment response to the bismuth-based quadruple therapy (P value = 0.28). CONCLUSIONS: Treatment with a bismuth-based quadruple therapy was effective in eradicating H. pylori infection in 78.3% of Saudi patients with an ITT analysis and in 87.8% as per-protocol analysis.